Clustering Microarray Data with Space Filling Curves - Vogiatzis, Dimitrios; Tsapatsoulis, Nicolas (My University, 2007)
We introduce a new clustering method for DNA microarray data that is based on space filling curves and wavelet denoising. The proposed method is much faster than the established fuzzy c-means clustering because clustering occurs in one dimension and it clusters cells that contain data, instead of data themselves. Moreover, preliminary evaluation results on data sets from Small Round Blue-Cell tumors, Leukemia and Lung cancer microarray experiments show that it can be equally or more accurate than fuzzy c-means clustering or a gaussian mixture model.
Keywords: Clustering; Space filling curve; Wavelets; Microarray DNA